2018
DOI: 10.1002/jwmg.21499
|View full text |Cite
|
Sign up to set email alerts
|

Western gray squirrel resource selection related to fire fuel management

Abstract: One of 3 populations of the state‐threatened western gray squirrel (Sciurus griseus) in Washington occurs in the northern Cascade Range (i.e., North Cascades), where long‐term fire suppression has increased the risk of catastrophic wildfire. Land management agencies throughout this region have implemented fire fuel reduction programs that alter squirrel habitat and may affect their populations. From April 2008 to September 2011, we investigated resource selection of 38 radio‐collared western gray squirrels at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…In contrast, western gray squirrels used some riparian areas on the Base but were largely found in uplands dominated by conifers with little shrub cover, consistent with studies elsewhere in Washington (Linders 2000, Gregory et al 2010, Stuart et al 2018). Linders (2000) indicated that some western gray squirrels briefly moved into riparian areas during breeding season to have young in tree cavities, and we observed similar behavior on the Base.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In contrast, western gray squirrels used some riparian areas on the Base but were largely found in uplands dominated by conifers with little shrub cover, consistent with studies elsewhere in Washington (Linders 2000, Gregory et al 2010, Stuart et al 2018). Linders (2000) indicated that some western gray squirrels briefly moved into riparian areas during breeding season to have young in tree cavities, and we observed similar behavior on the Base.…”
Section: Discussionsupporting
confidence: 80%
“…Occupancy of high‐use areas by female gray squirrels exclusive of other conspecific females was evident on the Base (Johnston 2013) and suggests that interference competition could explain some differences in resource use. We suggest, however, that eastern and western gray squirrels also differ in their preferred habitats based on our observations, experimental removals of eastern gray squirrels (Johnston 2013), and habitat associations of these squirrels reported elsewhere (Byrne 1979, Linders 2000, Gregory et al 2010, Stuart et al 2018).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations